THU0204 Relationships between methotrexate dosages and clinical variables in patients with rheumatoid arthritis who achieved remission with methotrexate monotherapy: a study using the iorra observational cohort study. (15th June 2017) - Tochihara, M; Katsumata, Y; Inoue, E; Kawaguchi, Y; Tanaka, E; Nakajima, A; Ikari, K; Taniguchi, A; Yamanaka, H
Abstract : Background: Considerable variability exists in the way rheumatologists prescribe methotrexate (MTX) therapy in patients with rheumatoid arthritis (RA), including the dosage [ref.1]. Start higher doses or fast dose escalation are associated with higher efficacy, but also with more toxicity. In addition, factors such as renal function, body size, and age of the patient can affect the optimal dosage of MTX. Objectives: We aimed to study the relationships between MTX dosages and clinical variables in patients with RA who achieved remission with MTX monotherapy. Methods: The "Institute of Rheumatology, Rheumatoid Arthritis (IORRA)" is a single-center prospective observational cohort study established at our institute in 2000. Data (physicians' and patients' disease assessments, laboratory data, and many other patient information) were collected from approximately 5, 000 RA patients biannually. More than 99% of RA patients treated at our institute were enrolled in this cohort, and >98% of patients answered and mailed their questionnaires back to us every time. Among the RA patients who were registered in the IORRA cohort study from 2011 through 2015, 603 patients fulfilled the American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) Boolean-based definition of remission in RA, at least once and used only MTX as disease-modifying antirheumatic drugs (DMARDs) including biological DMARDs for 5 years. Relationships between MTX dosages and gender, disease duration, height, body weight, body mass index, body surface area, serum creatinine (SCr), estimated glomerular filtration rate (eGFR), creatinine clearance (by Cockcroft-Gault Equation), rheumatoid factor, and anti-cyclic citrullinated peptide antibody when remission was first reached by each patient were analyzed by univariate analyses using Pearson correlation coefficient and Welch's t test. Subsequently, a multiple regression analysis was performed. Results: Univariate analyses detected several candidate clinical variables associated with MTX monotherapy dosages in RA patients who achieved remission: height, body weight, body surface area, SCr, eGFR, and CCr ( p =0.004, 0.050, 0.241, <0.001, <0.001, and <0.001, respectively). Subsequently, a multiple regression model developed a best-fit model with the following variables; age, height, body weight, and SCr (standardized partial regression coefficient = -0.20, 0.10, 0.07, and -0.22, respectively), while its adjusted coefficient of determination was 0.114. Conclusions: There were significant relationships between MTX monotherapy dosages and age, height, body weight, and renal function in RA patients who achieved remission. However, the low coefficient of determination indicated the model accounted for limited variability with the specified variables. References: Visser K and van der Heijde D. Optimal dosage and route of administration of methotrexate in rheumatoid arthritis: a systematic review of the literature. Ann Rheum Dis. 2009;68:1094. Disclosure of Interest: M. Tochihara: None declared, Y. Katsumata: None declared, E. Inoue: None declared, Y. Kawaguchi: None declared, E. Tanaka Consultant for: Abbvie, Eisai Pharmaceutical, Chugai Pharmaceutical, Bristol Myers Squibb, Astellas Pharmaceutical, Pfizer, Takeda Pharmaceutical, and Ayumi Pharmaceutical, Speakers bureau: Abbvie, Eisai Pharmaceutical, Chugai Pharmaceutical, Bristol Myers Squibb, Astellas Pharmaceutical, Pfizer, Takeda Pharmaceutical, and Ayumi Pharmaceutical, A. Nakajima Consultant for: Bristol-Meyers, Mitsubishi Tanabe Pharma, Nippon Kayaku Co. Ltd., Novartis Pharma, Pfizer, Siemens Healthcare Diagnostics K.K. and Takeda Pharmaceutical Company., Speakers bureau: Bristol-Meyers, Mitsubishi Tanabe Pharma, Nippon Kayaku Co. Ltd., Novartis Pharma, Pfizer, Siemens Healthcare Diagnostics K.K. and Takeda Pharmaceutical Company., K. Ikari Grant/research support from: Astellas, UCB, Bristol-Meyers, Pfizer, Eisai, Tanabe-Mitsubishi, Chugai, AbbVie, Janssen Pharmaceutical, Otsuka, Kaken, Asahi-Kasei, Hisamitsu and Takeda., Speakers bureau: Astellas, UCB, Bristol-Meyers, Pfizer, Eisai, Tanabe-Mitsubishi, Chugai, AbbVie, Janssen Pharmaceutical, Otsuka, Kaken, Asahi-Kasei, Hisamitsu and Takeda., A. Taniguchi Grant/research support from: AbbVie, Eisai, Takeda, Tanabe-Mitsubishi, Teijin Pharma, Pfizer., Speakers bureau: AbbVie, Eisai, Takeda, Tanabe-Mitsubishi, Teijin Pharma, Pfizer., H. Yamanaka Grant/research support from: MSD, Ayumi, AbbVie, Eisai, Ono, Astellas, Daiichi-Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, Nippon Shinyaku, Pfizer. UCB. Nippon Kayaku, YL biologics, Bayer and Bristol-Meyers., Consultant for: MSD, Ayumi, AbbVie, Eisai, Ono, Astellas, Daiichi-Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, Nippon Shinyaku, Pfizer. UCB. Nippon Kayaku, YL biologics, Bayer and Bristol-Meyers., Speakers bureau: MSD, Ayumi, AbbVie, Eisai, Ono, Astellas, Daiichi-Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, Nippon Shinyaku, Pfizer. UCB. Nippon Kayaku, YL biologics, Bayer and Bristol-Meyers.